Incidence and Risk Factors for Surgical Site Infections Following Oromaxillofacial Oncologic Surgery in Dogs - Rigby, Brittney E.; Malott, Kevin; Hetzel, Scott J.; Soukup, Jason W. (Frontiers in Veterinary Science, 2021)
Antibiotic stewardship in veterinary medicine is essential to help prevent resistant bacterial infections. Critical evaluation into the benefits of prophylactic use of antibiotics during veterinary surgical procedures is under reported and additional investigation is warranted. The objectives of this paper were to determine the incidence of surgical site infection in dogs that underwent oromaxillofacial oncologic surgery and to identify risk factors for the development of surgical site infection. In this retrospective cohort study including 226 dogs surgically treated for oromaxillofacial tumors between January 1, 1997 and December 31, 2018, the incidence of surgical site infection was determined to be 7.5%. Univariable logistical regression models were used to evaluate potential risk factors for development of surgical site infections including signalment, tumor type, antibiotic protocol, time under anesthesia, location of surgical procedure (dental suite vs. sterile operating room), specific comorbidities, and surgical margins obtained. Anesthetic events lasting greater than 6 h were significantly associated with development of infection. Signalment, comorbidities, administration of anti-inflammatory and immunosuppressive medications, tumor type, histological margin evaluation, surgical procedure location, and antibiotic protocols were not significant contributors to development of infection. Use of antibiotic therapy in this cohort was not protective against development of infection and may not be routinely indicated for all oromaxillofacial oncologic surgeries despite common promotion of its use and the contaminated nature of the oral cavity. Anesthetic time significantly contributed towards the development of infection and use of perioperative antibiotics for surgical procedures lasting >6 h may be routinely warranted.